Atomic ruthenium-riveted metal-organic framework with tunable d-band modulates oxygen redox for lithium-oxygen batteries - Lv, Qingliang (2023)
Non-aqueous Li-O2 batteries have aroused considerable attention because of their ultrahigh theoretical energy density, but they are severely hindered by slow cathode reaction kinetics and large overvoltages, which are closely associated with the discharge product of Li2O2. Herein, hexagonal conductive metal-organic framework nanowire arrays of nickel-hexaiminotriphenylene (Ni-HTP) with quadrilateral Ni-N4 units are synthesized to incorporate Ru atoms into its skeleton for NiRu-HTP. The atomically dispersed Ru-N4 sites manifest strong adsorption for the LiO2 intermediate owing to its tunable d-band center, leading to its high local concentration around NiRu-HTP. This favors the formation of film-like Li2O2 on NiRu-HTP with promoted electron transfer and ion diffusion across the cathode-electrolyte interface, facilitating its reversible decomposition during charge. These allow the Li-O2 battery with NiRu-HTP to deliver a remarkably reduced charge/discharge polarization of 0.76 V and excellent cyclability. This work will enrich the design philosophy of electrocatalysts for regulation of kinetic behaviors of oxygen redox.